Inovasi Pembuatan Nugget Sayur di Desa Tragah Bangkalan Madura: Solusi Sehat dan Lezat untuk Anak - Roidatus Shofiyah; Ufi’atun Nur Faizah; Mochammad Zain Al Majid (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to develop an innovation in vegetable nugget production as a healthy and tasty solution for children in Tragah Village, Bangkalan, Madura. Vegetable consumption among children remains low, impacting their nutritional intake. The vegetable nugget innovation is expected to enhance vegetable acceptance in an attractive and easy-to-consume form. This research uses a community action research (CAR) approach with a product development design, community trials, and product acceptance evaluation. Data were collected through interviews, observations, and questionnaires involving children and parents. The findings show that vegetable nuggets were well received by children, leading to an increased interest in vegetable consumption. Additionally, the product meets the nutritional standards for children. The implications of this study indicate that innovations in vegetable-based food products can be an effective solution to promote healthy eating habits among children, especially in rural areas.